(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Swami Vivekananda’s ideas on Philosophy of Education. According toSwami Vivekananda, education does not mean the mass of information which isinserted by force into the mind of a child. In his own words, education is themanifestation of perfection already reached man. Indian nationalism and spiritualismwere the basic foundations for his philosophy of education and the philosophyof Vedanta and Upanishads. He was against the system of contemporaryeducational system; it turned men into slaves, capable of slavery and nothingelse. He emphasized that the aim of education to be life-building, man-makingand character-making and also he said that knowledge without culture was onlyskin-deep. The mind is crammed with facts before it knows how to think.Self-development, fulfillment of Swadharma, freedom of growth and characterformation are the aims of education according to him. For him education meansthe process by which character is formed, strength of mind is increased andintellect is sharpened, as a result of which one can stand on one’s own feet.Real education is that which prepares a man for struggle of existence. Itprepares man for social service and develops his character. He has emphasizedthat an education which develops character, mental powers, and intelligencegives self-confidence and self-reliance among the individuals. SwamiVivekananda stressed education for democracy and national development.Education was a powerful instrument to achieve these developmental qualities inthe people. He wants to make the individual by giving recognizing of hiscultural heritage and to struggle throughout his life, so that he emphasizededucation is the right choice to upcoming of human beings. Vivekananda not onlypossessed high ideals of education but also he developed a sound system ofideals, how it was achieved.